Parental Knowledge and Its Association with Acute Respiratory Infection (ARI) In Toddlers : A Cross-Sectional Study at Cilandak Health Center, South Jakarta - Novia Afidatul Muayani; Rima Berlian Putri (STIKep PPNI Jawa Barat, 2025)
Background: Acute Respiratory Infection (ARI) is a leading cause of morbidity and mortality in children under five years, particularly in low- and middle-income countries. In Indonesia, ARI continues to contribute significantly to the disease burden in toddlers. One critical factor influencing ARI incidence is the level of parental knowledge regarding prevention and early detection of symptoms. Objective: This study aimed to determine the relationship between parental knowledge and the incidence of ARI in toddlers in the working area of Cilandak Health Center, South Jakarta. Methods: This study applied a correlational analytic design with a cross-sectional approach. A total of 77 respondents were selected using accidental sampling, consisting of parents with toddlers. Data were collected using structured questionnaires to assess the level of parental knowledge and the incidence of ARI in their children. Statistical analysis used Pearson correlation to test the relationship between variables. Results: The study found that 70.1% of parents had low knowledge about ARI, and 71.4% of toddlers had experienced ARI. The correlation test showed a very strong and significant negative relationship between parental knowledge and ARI incidence (p = 0.001; r = -0.906), indicating that higher knowledge levels are associated with lower ARI incidence in toddlers. Conclusion: There is a significant inverse relationship between parental knowledge and the incidence of ARI in toddlers. Enhancing parental knowledge through health education may help reduce the burden of ARI among young children.